"You can explore it more online": a qualitative study on Australian women's use of online health and medical information - Sarah Maslen; Deborah Lupton (BMC, 2018)
Abstract Background Previous research has demonstrated the importance of search engines, websites, online discussion groups and social media groups for women in developed countries looking for health and medical information, but few studies have focused on Australian women. The Australian Women and Digital Health Project was designed to investigate how Australian women from a range of age groups and locations used digital health technologies across the full spectrum available to them. The findings on their use of online information and decision-making in relation to seeking face-to-face medical advice are discussed in this article. Methods Qualitative research, including focus group discussions (24 participants) and face-to-face (12 participants) and telephone (30 participants) semi-structured interviews was conducted with a total of 66 Australian women aged between 21 and 74. The focus groups and interviews were transcribed and analysed using inductive thematic analysis sensitised by a feminist new materialism theoretical standpoint. This involved identifying the dimensions of affordances, relational connections, affective forces and agential capacities in the women's accounts. Results All participants regularly used online sources to find health information, advice and support. We identified six key agential capacities relating to these ways in which the women enacted online health information seeking: 1) self-screening; 2) preparing for and following up a consultation; 3) selective engagement; 4) caring for others; 5) creating and sharing new information; and 6) challenging medical authority. The affordances of accessibility and convenience of online sources, relational connections between women and trusted sources (both online and offline) and between women and family members on whose behalf they sought information and affective forces such as trust, the need for reassurance and frustration and anger with deficient healthcare services contributed to these capacities. Conclusions Women engaged in complex interactions with online information, actively and creatively using it in diverse ways in their negotiations with seeking face-to-face medical expertise. Their online practices generated a set of agential capacities that help them to assess whether they or their family members need medical attention, supplement or challenge the medical advice they have already received or generate and share their own information.